NEW CHRONOSTRATIC SCHEME OF SOUTH-EASTERN FENNOSCANDIA AND ITS USE IN THE PREPARATION OF SMALL-SCALE GEOLOGICAL MAPS OF THE PRECAMBRIAN REGIONS - V. S. Kulikov; V. V. Kulikova; A. K. Polin (Известия высших учебных заведений: Геология и разведка, 2017)
A new chronostratic scheme of South-East (SE) Fennoscandia has been developed, based on the International Stratigraphie Scale, taking into account some elements of the Common Stratigraphic Scale of Russia and the regional stratigraphic scheme of the North-West (NW) of Russian Federation. A rank of Archean and Proterozoic stratons has been determined (including supersystems for Riphean and Archean geonotems), compatable in dutation to the Phanerozoic systems (Mesozoic and Paleozoic ones). An original coloring for the geological maps of the newly allocated systems and their analogues in the Precambrian, as well as the digital indexing of all stratons of the rank of systems instead of the traditional alphabetic one, have been proposed. Based on the extensive geological materials of the Institute of Geology of Karelian Research Centre of the Russian Academy of Sciences, in view of the new approaches and reliable geochronological data, an areal geological map of SE Fennoscandia in scale 1: 750 000 has been created, which includes the territory of Karelia and adjacent areas of the Russian Federation and eastern Finland. The proposed chronostratic scheme can serve as a basis for developing legends of small-scale state geological maps of the new generation, especially in the regions of the Precambrian development.